Analisis Pola Pembelian Toys Dengan Menggunakan Metode Algoritma Apriori - Aliyah, Siti (STIKOM Tunas Bangsa Pematangsiantar, 2020)
The priority algorithm is an analysis of habits that occur in purchases by looking for the association rule from different itemsets. The calculation is carried out to determine the minimum value of support and minimum confidence that will produce the association rule; the association rule is used to produce the percentage of purchasing activities against the itemset within a certain period using the weka application. The results of the best using the a priori algorithm method show that the association rule, under which the customer often buys a doll stage and an alphabet puzzle that has met the minimum value of confidence.